The earthquake under the action of underground structure and the influence of the distance between adjacent buildings. Issue 1 (June 2021) - Liu, Pengjun; Zheng, Guodong; Zhang, Qishuo
Abstract: With the large-scale construction of urban rail transit in China, subways often cross the bottom of surface buildings or are located near them. In order to study the complex catastrophic correlation effects of the underground structure of the subway, the soil and the adjacent existing structures under earthquakes. We carried out numerical simulation calculations to study the effects of underground structures and adjacent existing structures under earthquakes. The interaction law of nearby existing buildings, the influence mechanism of the neighboring building's depth factors on the seismic response of the complex system, and the system's seismic response law were determined.